THE IRRIGATION SCHEDULING IGDROID TOOL - RODRIGUES, DIOGO FRANSCISCO BORBA; ALMEIDA, CERES DUARTE GUEDES CABRAL DE (IRRIGA, 2014)
THE IRRIGATION SCHEDULING IGDROID TOOL DIOGO FRANSCISCO BORBA RODRIGUES¹ E CERES DUARTE GUEDES CABRAL DE ALMEIDA² 1 Doutorando, Programa de Pós-Graduação em Engenharia Agrícola, Universidade Federal Rural de Pernambuco, diogo.borbar@gmail.com 2 Engenheira Agrônoma, Profª Doutora, Colégio Agrícola Dom Agostinho Ikas, Universidade Federal Rural de Pernambuco, ceres@codai.ufrpe.br 1 ABSTRACT The speed of information processing of data collected in fields can be a deciding factor in the efficiency of an irrigation system, responding appropriately to crops' water requirements. The objective of this paper was to describe a new tool for irrigation scheduling, called IGdroid. This tool is a mobile phone application for use by farmers who use irrigation and have some climate monitoring equipment, such as rain gauges and evaporation pans, providing irrigation advice in areas based on inputs and outputs data without internet connection. The development process and the main functions of the application are described in this paper. The software is inserted in the farmer's mobile phone to schedule everyday irrigation. Soil properties, irrigation system and crop data must be inserted in the database, so the farmer can insert climatological data in her/his mobile phone on a daily basis. The application can record multiple irrigated areas with different crops, soil types and irrigation systems, and reports irrigation requirements daily. If the farmer needs to irrigate, the app informs her/him of the water depth (mm) and how long to run the system (in hours) in each area. This app also allows simulation of irrigation scenarios in agricultural planning. Keywords: irrigated agriculture, Android, App Inventor